Evaluation and Feasibility of Different Models and Methods for Composite Simulation Using Ansys - Bonhin, Eduardo Pires [UNESP]; Müzel, Sarah David [UNESP]; Oliveira, Geraldo Cesar Rosario de [UNESP]; Tupinambá, Walter Luiz Medeiros; Guidi, Erick Siqueira [UNESP]; Silva, Carlos Alexis Alvarado; Silva, Fernando de Azevedo [UNESP] (My University, 2024)
The utilization of composite materials in various engineering sectors has gained significant prominence due to their unique characteristics. However, owing to their inherent heterogeneity, these materials often exhibit nonlinear and unpredictable behaviors. Consequently, the finite element method has seen a growing application as an invaluable tool for analyzing composites subjected to diverse scenarios. This study aims to assess the advantages and disadvantages of ANSYS APDL and Workbench modules (specifically, ACP and Static Structural) while also examining the impact of the choice of elements in simulating composite materials. The results obtained reveal that, irrespective of the chosen method and element type, the strain patterns exhibited remarkable similarity. Nonetheless, models employing shell elements demonstrated a notable advantage, requiring fewer elements and nodes. Furthermore, the recommended model is the integrated ACP model. This preference is based in its capacity to simplify layer modeling and enable the detailed analysis of strains within each layer.
Keywords: Carbon Fibers; Finite Element; Materials; Polyphenylene Sulfide Composite